Robust portfolio choice under the interest rate uncertainty. (2nd September 2022) - Gajek, Lesław; Krajewska, Elżbieta
ABSTRACT: In this paper, we investigate a portfolio selection which is robust with respect to the interest rate uncertainty. For the portfolios with random assets, liabilities and interest rates, we bound from above Value-at-Risk of the change in the portfolio value, due to the interest rate model violation. Next, we find the robust portfolio applicable for a wide range of model perturbations. The robust optimization problem is treated in general and under additional restrictions, for example, on the expected duration of the portfolio. The results are based on the Hilbert space geometry methods applied to incomplete markets.